Reading Canada and the Postmodernist Culture in Linda Hutcheon’s The Politics of Postmodernism - Singh, Alka (Journal of Applied Cultural Studies, 2016)
Linda Hutcheon, one of the foremost Canadian critics of the day, in her famous work The Politics of Postmodernism, seems to find herself initially in a dilemma. She attempts an elucidation of what postmodernism is and what it is not, recognizing its both positive and negative dimensions. The present paper focuses on the literary culture in Canada, and the manifestation of postmodernist traces therein, with a special reading of Hutcheon’s The Politics of Postmodernism.